Implementation of the Roles and Functions of the School Committee in Improving the Quality of Education Services in the City of Cirebon - Naufalia Nuraya; Adiman Adiman; Endang Sri Budi Herawati; Jumira Warlizasusi; Rusi Rusmiati Aliyyah (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Parental support in improving the quality of education services in schools is needed. Awareness of the importance of quality education will help schools as education providers to realize quality education. There is a need for the support of the school committee as a forum for the participation of parents in education. This study wants to describe the implementation of the role and function of the school committee in supporting the improvement of education quality services at SMAN 9 Cirebon City. The data was collected through in-depth interviews, questionnaires, and documentation studies. The results showed that in general, the school committee of has school carried out all its roles and functions, although not yet optimal. School committees consider more related to school programs that need to be implemented but are not covered by school finances. Communication with alumni is well established and has even been able to contribute to the renovation of the school mosque. Efforts to provide non-financial support are carried out by establishing communication and comparative studies with other schools deemed to have a better quality infrastructure. The results of the comparative study are arranged in a priority program to support the progress of the quality of education services.